2020
DOI: 10.1001/jama.2020.10218
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Convalescent Plasma for COVID-19—Potentially Hopeful Signals

Abstract: Convalescent plasma for the treatment of infectious diseases has been used since the early 20th century and was associated with reduced mortality during the 1918 influenza, 1 2003 SARS, 2 and 2009 influenza H1N1 3 pandemics. However, most published studies of these diseases were case series and retrospective comparisons of treated and nontreated individuals. Consistent with this, several uncontrolled case series of convalescent plasma use in patients with coronavirus disease (2019) COVID-19 have suggested a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
83
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 15 publications
2
83
0
4
Order By: Relevance
“…2,3 However, only a very limit evidences has been showed it is effective in COVID-19 treatment. 4,5 Here, we describe the first successful recovery of case of COVID-19 in a KTR treated with convalescent plasma therapy.…”
Section: Dear Editormentioning
confidence: 96%
“…2,3 However, only a very limit evidences has been showed it is effective in COVID-19 treatment. 4,5 Here, we describe the first successful recovery of case of COVID-19 in a KTR treated with convalescent plasma therapy.…”
Section: Dear Editormentioning
confidence: 96%
“…We previously demonstrated that passive transfer of monoclonal antibodies against SARS-CoV-2 S protein reduced viral titers and pathology in the lungs in a mouse model of SARS-CoV-2 (3). Monoclonal antibodies engineered from neutralizing antibodies, initially identified from convalescent COVID-19 patients, have been advanced as potential antiviral therapeutics (4)(5)(6), and early results from convalescent plasma use in patients indicate a protective effect of antibodies against SARS-CoV-2 (7)(8)(9)(10). While early results are promising, the antibody titer conferring protection remains unclear and the role of neutralizing antibodies in protection has not been fully elucidated (11).…”
Section: Introductionmentioning
confidence: 99%
“…Many strategies to combat COVID-19 are currently being implemented; among them include contact tracing, convalescent plasma therapy, anti-viral drug therapy, and vaccine development (6)(7)(8)(9). Here, we focus on vaccine development.…”
Section: Introductionmentioning
confidence: 99%